IDENTIFIKASI KESALAHAN PESERTA DIDIK KELAS VIII SMP NEGERI 1 PRAMBON DALAM MEMECAHKAN MASALAH LINGKARAN - Aris Mustofa; Sudirman Sudirman; Makbul Muksar (Jurnal Kajian Pembelajaran Matematika, 2020)
Error is a deviation from the correct algorithm. Every student has the possibility of making mistakes in working onproblem solving problems, both fact errors, concept errors and procedural errors. Mistakes made by students can beused as a reference in knowing the difficulties they experienced. Identifying the results of students' solving in solvingproblems solving problems is one of the efforts to help students who experience errors. The purpose of this study is toidentify and describe students' mistakes in solving circle problems. The research instrument used was a test. The subjectsof this study were 33 students of eighth grade 1 Prambon Junior High School. Based on the identification of students'answers that work on problem solving there are three types of mistakes made which include factual errors, concepterrors and procedural errors.